Digital financial literacy, social capability, dan financial resilience di era digital - Cindi Ferdiani; Anna Widiastuti; Hadi Ismanto (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2026)
This study aims to examine the effects of digital financial literacy and social capability on household financial resilience, with financial capability and fintech usage as mediators. A quantitative approach was employed using a survey of households in Indonesia. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that digital financial literacy has a significant effect on financial resilience through financial capability and fintech usage. Furthermore, financial capability serves as a key mediator in the relationships between both digital financial literacy and social capability with financial resilience. Meanwhile, fintech usage mediates the effect of digital financial literacy on financial resilience, but does not mediate the relationship between social capability and financial resilience. These findings suggest that the adoption of financial technology is driven more by individual literacy and cognitive capacity than by social factors. This study highlights the importance of strengthening digital financial literacy and financial capability as strategic pathways to enhance household financial resilience in the digital era